Comércio Eletrônico no Brasil: evidências para três empresas do setor de varejo no período de 2020 e 2021 - Melo, Thiago de Souza (Brasil, 2023)
E-commerce is increasingly becoming a successful sales model. In 2020, companies in the retail sector had their economies impacted by the COVID-19 pandemic, needing to find a way to stay active and make sales, seeking strategies to survive such a market abnormality. The objective of this work is to study the effects generated by the pandemic on publicly traded companies in the retail sector, namely: Magazine Luiza, Via Varejo and Americanas. In addition, to evaluate the impact of the 2020 and 2021 periods on e-commerce, trying to understand which strategies these companies used to leverage their sales. Primary data from the management reports and financial reports of each of the mentioned companies were used. Evidence was found that proves that the use of multichannel, social networks and marketplace contributed to the success of e-commerce for the three companies in the sample.